A study on the sustainability assessment of China’s basic medical insurance fund under the background of population aging–evidence from Shanghai - Yu, Zhi-Qing; Chen, Li-Peng; Qu, Jun-Qiao; Wu, Wan-Zong; Zeng, Yi (Frontiers in Public Health, 2023)
Objective: As China’s population aging process accelerates, the expenditure of China’s basic medical insurance fund for employees may increase significantly, which may threaten the sustainability of China’s basic medical insurance fund for employees. This paper aims to forecast the future development of China’s basic medical insurance fund for employees in the context of the increasingly severe aging of the population. Methods: This paper taking an empirical study from Shanghai as an example, constructs an actuarial model to analyze the impact of changes in the growth rate of per capita medical expenses due to non-demographic factors and in the population structure on the sustainability of the basic medical insurance fund for employees. Results: Shanghai basic medical insurance fund for employees can achieve the goal of sustainable operation in 2021-2035, with a cumulative balance of 402.150-817.751 billion yuan in 2035. The lower the growth rate of per capita medical expenses brought about by non-demographic factors, the better the sustainable operation of the fund. Conclusions: Shanghai basic medical insurance fund for employees can operate sustainably in the next 15 years, which can further reduce the contribution burden of enterprises, which lays the foundation for improving the basic medical insurance treatment for employees.